“Comme espics dans les plaines”: Patterns of Translation of Robert Garnier’s Epic Similes in Thomas Kyd’s Cornelia (1594) - Belle, Marie-Alice (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2017)
Although celebrated in its time as a worthy contribution to the poetic experiments of the late Elizabethan age, Thomas Kyd’s 1594 Cornelia, translated from Robert Garnier’s Cornélie (1574), has long been held by modern criticism as a minor work in the playwright’s career. Previous attempts to rehabilitate the dramatic and poetic values of Kyd’s translation have focused on the metaphoric networks that underlie Kyd’s appropriation of Garnier’s play or on the political aspects of Kyd’s treatment of historical figures and themes. This article examines more specifically Kyd’s approach to Garnier’s epic similes—many of which are actually borrowed from both classical authors and contemporary poets. By exploring the inter-generic and intertextual connections established in Kyd’s translation, this article maps out the literary and cultural trajectories involved in the appropriation and emulation of Continental tragic models, thus highlighting Kyd’s experiments with various kinds of drama, clarifying the play’s connection with the productions of the Sidney-Herbert “circle,” and establishing its significance in late Elizabethan literary culture.